Financial management practices: Inefficiencies for self sustainable on donor funded water projects the case study of Global Water Initiatives Program phase I - Mapunda, Keneth Njako (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for award of the degree of Master of Science in accounting and finance of Mzumbe University